Hierarchical three-dimensional NiCo2O4 nanoneedle arrays supported on Ni foam for high-performance supercapacitors1. Issue 32 (10th April 2015) - Wu, Jian; Mi, Rui; Li, Shaomin; Guo, Pan; Mei, Jun; Liu, Hao; Lau, Woon-Ming; Liu, Li-Min
<x xml:space="preserve">Abstract</x> A novel NiCo2O4 nanoneedle arrays with bottom crosslinked nanosheets grew on Ni foam as advanced binder-free electrodes via a facile one-step hydrothermal method followed by annealing in air, which exhibited high electrochemical performance.